2014
DOI: 10.1093/gerona/glu182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inspiratory Muscle Training in Elderly Women on Respiratory Muscle Strength, Diaphragm Thickness and Mobility

Abstract: Inspiratory muscle training of moderate intensity improves respiratory muscle strength, diaphragm thickness, and diaphragm mobility in elderly women and it should be considered to minimize changes associated with senescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 40 publications
4
67
0
8
Order By: Relevance
“…Importantly, CHF patients who undergo IMT pre-surgery have fewer pulmonary complications post-surgery [199]. Recent studies are emerging that suggest potential benefits of inspiratory resistance training in healthy older adults as well [84,200]. In older subjects, inspiratory muscle training increases peak inspiratory flow [84].…”
Section: Therapeutic Strategies To Counteract Inspiratory Dysfunctionmentioning
confidence: 99%
“…Importantly, CHF patients who undergo IMT pre-surgery have fewer pulmonary complications post-surgery [199]. Recent studies are emerging that suggest potential benefits of inspiratory resistance training in healthy older adults as well [84,200]. In older subjects, inspiratory muscle training increases peak inspiratory flow [84].…”
Section: Therapeutic Strategies To Counteract Inspiratory Dysfunctionmentioning
confidence: 99%
“…On the other hand, Albuquerque et al, [15] demonstrates that six weeks of PR-IMT training was enough to improve the inspiratory muscle strength and functional capacity in physically active elderly subjects with intensity of 40%-70% of MIP. Both Souza et al, [3] and Albuquerque et al, [15] showed no change in lung volumes as stated by Enright and Unnithan [12]. In contrast, TURNER et al [8] reported that six weeks training period using PR-IMT in asthmatic patients with a moderate load of 50% improved MIP, tolerance and perception of dyspnea.…”
Section: Introductionmentioning
confidence: 92%
“…The effectiveness of these devices has been proved in Turner et al, [7,8] which stated that the PR-IMT devices work on improving the maximal inspiratory pressure (MIP). In International Journal of Physical Medicine & Rehabilitation addition, proved that there is an improvement in MIP [3], maximal expiratory pressure (MEP), diaphragm mobility and thickness.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations